Immunoevasive Pericytes From Human Pluripotent Stem Cells Preferentially Modulate Induction of Allogeneic Regulatory T Cells. (9th September 2014) - Domev, Hagit; Milkov, Irina; Itskovitz-Eldor, Joseph; Dar, Ayelet
Abstract: Isolated microvessel-residing pericytes and pericytes from human pluripotent stem cells (hPSCs) exhibit mesenchymal stem cell-like characteristics and therapeutic properties. Despite growing interest in pericyte-based stem cell therapy, their immunogenicity and immunomodulatory effects on nonactivated T cells are still poorly defined, in particular those of vasculogenic hPSC pericytes. We found that tissue-embedded and unstimulated cultured hPSC- or tissue-derived pericytes constitutively expressed major histocompatibility complex (MHC) class I and the inhibitory programmed cell death-ligand 1/2 (PD-L1/2) molecules but not MHC class II or CD80/CD86 costimulatory molecules. Pretreatment with inflammatory mediators failed to induce an antigen-presenting cell-like phenotype in stimulated pericytes. CD146 + pericytes from hPSCs did not induce activation and proliferation of allogeneic resting T cells independent of interferon (IFN)-γ prestimulation, similarly to pericytes from human brain or placenta. Instead, pericytes mediated a significant increase in the frequency of allogeneic CD25 high FoxP3 + regulatory T cells when cocultured with nonactivated peripheral blood T cells. Furthermore, when peripheral blood CD25 high regulatory T cells (Tregs) were depleted from isolated CD3 + T cells, pericytes preferentially induced de novo formation of CD4 + CD25 high FoxP3 + CD127 −, suppressive regulatory T cells. Constitutive expression of PD-L1/2 and secretion of transforming growth factor-β by hPSC pericytes directly regulated generation of pericyte-induced Tregs. Pericytes cotransplanted into immunodeficient mice with allogeneic CD25 − T cells maintained a nonimmunogenic phenotype and mediated the development of functional regulatory T cells. Together, these findings reveal a novel feature of pericyte-mediated immunomodulation distinguished from immunosuppression, shared by native tissue pericytes and hPSC pericytes, and support the notion that pericytes can be applied for allogeneic cell therapy. Abstract : This study tested the adaptive alloimmunity response of nonactivated human T cells to human pluripotent stem cell (hPSC)-derived pericytes compared with that of pericytes from brain and full-term placenta in cocultures and following implantation into immunodeficient mice. It was found that under steady-state conditions, hPSC pericytes, like their native tissue-derived counterparts, maintained poor immunogenicity and immunomodulation capabilities, favoring allostimulation of regulatory T cells over T-cell activation.